Total Induced Vertex Stress in Barbell-Like Graphs - Joseph Shiny; Johan Kok; V. Ajitha (Journal of the Indonesian Mathematical Society, 2021)
This paper introduces new parameters called induced vertex stress and total induced vertex stress in G, respectively. For graphs G and H, aspects of the maximum and minimum total induced vertex stress that can be obtained by 1-edge addition and 2-vertex merging are discussed.